A Method for the Prescriptive Assessment of the Flow of Information Within Organizations - Delehanty, Thomas; Sullo, Pasquale; Wallace, William A. (Management Science, 1982)
Research on information flow in organizational networks has focused on structural aspects and the identification and location of special communicators or “gatekeepers.” In this paper, the methods of system reliability are adapted to the systematic analysis of information flow networks; in this context, system reliability is the probability of information flow between the information source and the ultimate recipient, while arc reliability is the probability of information flow on that arc. Gatekeepers generally differ from other nodes in the network by virtue of their greater number of and more reliable incoming and outgoing arcs. Through methods illustrated here, gatekeepers, as well as other nodes and their connecting arcs, can be assessed with respect to their contribution to system effectiveness (reliability). With this analytical capability, the manager can explore and assess alternate courses of action in order to adopt those which most enhance system effectiveness. The approach is illustrated by application to two representative studies from the literature on information flow in R&D organizations.